2020
DOI: 10.1051/e3sconf/202015101025
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fasciola gigantica and Paramphistomum spp Infection in Aceh Cattle

Abstract: Fasciola gigantica and Paramphistomum spp. are trematode helminth causing severe economic losses in cattle farming in Aceh Province, Indonesia. This study was conducted to examine the correlation between the prevalence of F. gigantica and Paramphistomum spp infections with the body condition and sex of Aceh cattle. In total, 103 cattle (50 males and 53 females) from an abattoir in Banda Aceh were used. The body condition score was recorded and the number of fluke eggs in feces was examined coproscopically. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
2
17
2
1
Order By: Relevance
“…and Planorbis spp. [28]. These two intermediate snail hosts play an active role in the transmission of snail-borne trematode infections.…”
Section: Discussionmentioning
confidence: 99%
“…and Planorbis spp. [28]. These two intermediate snail hosts play an active role in the transmission of snail-borne trematode infections.…”
Section: Discussionmentioning
confidence: 99%
“…These flukes will interfere the metabolism of lipid, proteins, and carbohydrate which cause growth disorder, low body weight, anemia, and even death. This fluke usually infects cattle, buffalo, sheep, goat, and other ruminants [1][2][3]. Mehmood et al [4] reported that fascioliasis caused financial losses approximately over 3.2 US$ billion/year worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Fasciolosis, helminthiasis caused by F. gigantica and Fasciola hepatica (F. hepatica) is widespread in cattle, sheep, and other ruminants which cost a great deal of economic loss [1][2][3]. Fasciolosis usually has no significant clinical symptoms, in chronic infection, it will cause severe weight loss, low milk production, infertility [2,4], and liver cirrhosis [5]. The disease is not only restricted in ruminants, but also reported in human, and a wide population is at high risk [6][7][8].…”
Section: Introductionmentioning
confidence: 99%